2016
DOI: 10.1007/s12298-016-0394-7
|View full text |Cite
|
Sign up to set email alerts
|

Imperative roles of salicylic acid and nitric oxide in improving salinity tolerance in Pisum sativum L.

Abstract: This study was undertaken to scrutinize efficacy of salicylic acid (SA) and/or sodium nitroprusside [SNP, source of nitric oxide (NO)] to mitigate injury symptoms of saline stress in L. Exposure to sodium chloride (NaCl) was found to be injurious to germinating. L. (var. Shubhra IM-9101) and a direct correlation between severity of toxicity and NaCl-concentrations could be discernible. Both SA and NO serves as signal molecules in plant stress responses, and play crucial roles in key regulatory pathways of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…In our study, SNP pre-treatment alleviated the detrimental effects of NaCl stress on seedling growth. These results have also been shown in many plant species exposed to NaCl stress (4,7,8). It has been reported that NO can loosen the cell wall, affect the phospholipid layer, increase membrane fluidity, and promote plant growth by increasing cell expansion (21).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In our study, SNP pre-treatment alleviated the detrimental effects of NaCl stress on seedling growth. These results have also been shown in many plant species exposed to NaCl stress (4,7,8). It has been reported that NO can loosen the cell wall, affect the phospholipid layer, increase membrane fluidity, and promote plant growth by increasing cell expansion (21).…”
Section: Discussionsupporting
confidence: 66%
“…Dong et al (22) re-ported that NO increases stem and root elongation by improving cytoplasmic viscosity and increasing the osmotic pressure under high salinity. However, it has been demonstrated that NO-mediated induction of salt tolerance is associated with increased activities of antioxidant enzymes and the accumulation of osmoprotectans (4,8). Additionally, NO has been shown to interact with salicylic acid and hydrogen peroxide to mediate the elimination of oxidative damage in many stress conditions (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NO improved the salt tolerance of Jatropha curcas during the establishment of seedlings by inducing an effective antioxidant system, thus inhibiting toxic ions and ROS accumulation, alleviating oxidative stress, and activating the antioxidant defense system [100]. Further, the application of sodium nitroprusside (source of NO) significantly mitigated growth inhibition and enhanced the contents of antioxidants and osmoprotectants in salt-challenged Pisum sativum L. [99]. Moreover, the NO donor sodium nitroprusside upregulated antioxidant defense mechanisms and increased ascorbic acid (AsA) contents and total phenolic contents (TPC), thereby effectively increasing the growth and grain yield of wheat under salinity stress [1] (Table 3).…”
Section: Salt Stressmentioning
confidence: 98%
“…Exogenous application of a NO donor i.e . sodium nitroprusside (SNP) has been shown to involve in the amelioration of several abiotic stresses . A number of studies have been shown that NO plays a protective role in a variety of physiological processes such as seed germination, growth and development, iron availability, and adaptive responses of plants to abiotic stresses .…”
Section: Introductionmentioning
confidence: 99%